A Multimodal Critical Discourse Analysis of “Garnier Sakura White” Advertisement - Marcella Pricilia; Ichwan Suyudi (International Journal of English and Applied Linguistics (IJEAL), 2023)
Television ads are one of the many types of mass media advertisements that inevitably surround people's lives today. It is a multimodal discourse in which the text consists of complex meaning resources. The objective of this research is to analyze the multimodality of the "Garnier Sakura White" television ads and determine the meaning that the producers intend to convey through this advertising image. This research analyzes it using multimodal discourse analysis, multimodal discourse analysis is required to delve deeper into the meaning or message to be conveyed through an advertisement. The research methods used in this research is descriptive research with qualitative methods. The result of this research show that the Garnier Sakura White advertisement contains a multimodal semiotic system. Linguistics and non-linguistics features both have mutually sustainable meanings, and each multimodal semiotic system is closely connected to produce advertising meaning and semiotics. Also, the message or purpose of this advertisement is quite comprehensive and easily understood by the audience.